2011
DOI: 10.1111/j.1442-2018.2011.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Views of Iranian patients on life with cancer: A phenomenological study

Abstract: Cancer is one of the major causes of death worldwide. The diagnosis of this disease can cause significant stress, which destroys the patient's hopes, dreams and expectations. The aim of this qualitative phenomenological study was to explore the perceptions of 23 Iranian patients about life with cancer using in-depth and semi-structured interviews as the method of data collection. The data were analyzed using Benner's interpretive thematic analysis method. Four main themes were clarified by studying the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…First, the results showed that Iranian cancer patients have many supportive care needs in different domains. By considering this results with this fact that there is no formal and designed supportive care programs for Iranian cancer patients, 28 it is obvious that there is emergency need for designing and implementation of this programs for Iranian cancer patients. Second, the results showed that in present context the focus of such programs should be on informational and physical and daily living needs of patients.…”
Section: Discussionmentioning
confidence: 98%
“…First, the results showed that Iranian cancer patients have many supportive care needs in different domains. By considering this results with this fact that there is no formal and designed supportive care programs for Iranian cancer patients, 28 it is obvious that there is emergency need for designing and implementation of this programs for Iranian cancer patients. Second, the results showed that in present context the focus of such programs should be on informational and physical and daily living needs of patients.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that there is no any established study aimed at providing supportive care for Iranian cancer patients. [33] On the other hand, Iranian health care providers and family members of cancer patients avoid from giving information about the cancer to cancer patients. So, many Iranian cancer patients do not have accurate perception about the prognosis of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…Dignity is a main part of human rights (Parmar et al, 2014) and preserving and enhancing patients' dignity is one the essential part of nursing care (Jacobson, 2007;Nasrabadi et al, 2011). The importance of patient dignity is also reflected in various nursing codes of ethics worldwide (International Council of Nurses, 2001;Sanjari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%